La gestión de la investigación en clave prospectiva. Acerca del futuro de la producción, transferencia y vinculación del conocimiento científico en la Universidad Nacional de La Matanza - Levy, Melina (2024)
The specialized literature on knowledge management has barely addressed the ability to obtain systematic information as an input that supplies planning in higher education, as well as the difficulties that universities encounter in obtaining such information. More recently, however, the study of future scenarios has become a valuable tool for analyzing the tensions and challenges that any organization should consider when planning. For this reason, this paper seeks to analyze the challenges that the research productivity of the Universidad Nacional de La Matanza scientists could face by 2030 from a management perspective. The methodology used was prospective. It considered the perspective of experts in charge of formulating specific policies to improve knowledge production in academic departments within the framework of the transversal norms designed by the Secretary of Science and Technology. Our aim is to make two contributions. The first is to produce theoretical knowledge for the field of science, technology and society (in Spanish, CTS); and, on the other hand, we expect to make a contribution to management.